2019
DOI: 10.1111/bjd.18316
|View full text |Cite
|
Sign up to set email alerts
|

Cutibacterium acnes in acne pathophysiology – the chicken or the egg?

Abstract: Linked Article: Ramasamy et al. Br J Dermatol 2019; 181:691–699.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…25 Acne vulgaris is a complex disease with multiple interacting pathogenic factors, and its pathogenesis is still not completely understood. 26 The current animal models for acne pharmacodynamic research, such as the ear swelling model and the rabbit ear anti-keratinization model, these models primarily focus on a single pathogenic factor and are limited in their ability to fully reflect the pathological characteristics of the disease, particularly the interaction of multiple pathogenic factors, which is similar to that observed in human acne. To gain a more comprehensive understanding of the pathogenesis of acne and to better assess the effectiveness of anti-acne drugs, it is imperative to develop an animal model that more closely reflects the pathogenesis of human acne.…”
Section: Discussionmentioning
confidence: 99%
“…25 Acne vulgaris is a complex disease with multiple interacting pathogenic factors, and its pathogenesis is still not completely understood. 26 The current animal models for acne pharmacodynamic research, such as the ear swelling model and the rabbit ear anti-keratinization model, these models primarily focus on a single pathogenic factor and are limited in their ability to fully reflect the pathological characteristics of the disease, particularly the interaction of multiple pathogenic factors, which is similar to that observed in human acne. To gain a more comprehensive understanding of the pathogenesis of acne and to better assess the effectiveness of anti-acne drugs, it is imperative to develop an animal model that more closely reflects the pathogenesis of human acne.…”
Section: Discussionmentioning
confidence: 99%
“…These factors are interconnected, such as due to the increased sebum production where many lipophilic bacteria like Cutibacterium acnes proliferate. These bacteria produce free fatty acids due to the lipase enzyme, which provokes the cells to secrete IL-1α and other cytokines to induce inflammatory responses and contribute to acne production [ 7 ]. According to earlier studies, C. acnes were responsible for acne; however, recent studies have shown that dysbiosis of facial microbiota plays a significant role in acne production [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Presently, through the popularization of high‐throughput sequencing technology, 10–12 researchers have found that the incidence of acne is related to microbiome diversity 13 . Other microbes, including Staphylococcus , 14 Demodex , 15,16 and Malassezia , 17 may be involved in the pathogenesis of acne, making the status of skin microflora in the pathogenesis of acne unclear 8,18,19 …”
Section: Introductionmentioning
confidence: 99%
“…13 Other microbes, including Staphylococcus, 14 Demodex, 15,16 and Malassezia, 17 may be involved in the pathogenesis of acne, making the status of skin microflora in the pathogenesis of acne unclear. 8,18,19 Photodynamic therapy (PDT) combines a photosensitizer and light source to generate reactive oxygen species. 20 PDT is a safe and effective method for the treatment of severe acne.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation